The Role of Transcendence Values in Preventing Intolerance Behavior - Muhtar Arifin; Khudzaifah Dimyati (Journal of Transcendental Law, 2021)
Intolerance behavior is a behavior that is very well known in human life. Even though it has been enacted by law for decades, the phenomenon of intolerance is still common in society. The research method used here is qualitative in nature which relies on literature in the form of books, books and journals related to the discussion. Among the conclusions obtained is that transcendent values have an important role in preventing intolerance behavior and attitudes. Among these values is to realize that difference is a sunnatullah that exists in creatures. The existence of this difference is a sign of Allah's power, including differences in ethnicity, language, color, nation and religion. In addition, the original law in interacting with fellow humans is peace. Prioritizing noble character in interacting is also a damper for the atmosphere in society and a deterrent to unwanted conditions. Recognizing and remembering that there is a reward in every good and sin in every bad thing can prevent someone from acting and acting in an intolerant nature.Keywords: transcendence value, prevent, intolerance.